Pediatric intestinal pseudo-obstruction: an international survey on diagnostic and management strategies in the European Reference Network for Rare Inherited and Congenital Anomalies Intestinal Failure Teams - Mutanen, Annika; Demirok, Aysenur; Wessel, Lucas; Tabbers, Merit (Journal of pediatric gastroenterology and nutrition, 2023)
Objectives: - Pediatric intestinal pseudo-obstruction (PIPO) management is based on nutritional, medical, and surgical care while available evidence is scarce. The aim of this study was to outline the current diagnostic and management strategies in intestinal failure (IF) teams of the European Reference Network for rare Inherited and Congenital Anomalies (ERNICA) and to compare these practices to the latest PIPO international guidelines. - Methods: - An online survey on institutional diagnostic and management strategies of PIPO was conducted among the ERNICA IF teams. - Results: - In total, 11 of 21 ERNICA IF centers from 8 countries participated. On average, 64% of teams had ≥6 and 36% had 1-5 PIPO patients under active follow-up. In total, 80 of 102 PIPO patients were parenteral nutrition (PN) dependent while each IF team had median 4 (range 0-19) PN dependent PIPO patients under follow-up. On average, each center received 1-2 new PIPO patients per year. Diagnostics mostly followed current guidelines while medical and surgical management strategies were diverse. - Conclusions: - Numbers of PIPO patients are low and management strategies are diverse among ERNICA IF teams. To improve PIPO patient care, regional reference centers with specialized multidisciplinary IF teams and continuous collaboration across centers are needed.
Gesehen am 28.08.2023